Increasing Knowledge for Social Assistance Recipients Through Family Development Sessions (FDS) of the Family Hope Program (PKH) in Indonesia - Umasugi, Mohbir; Adam, Muhammad Darsan Hi (Yayasan Ilomata, 2024)
One of the strategic and priority programs of the Indonesian government is the Family Hope Program (PKH) under the Ministry of Social Affairs. PKH itself is a program designed to alleviate poverty with poverty levels ranging from 0% to 10%. There is a PKH social assistant who is a program implementer with the function of carrying out socialization, validating data, verifying commitment to recipients of PKH social assistance in education, health, and social welfare services, updating data, facilitating, mediating and advocating to receive complementary program assistance, and hold family capacity building meetings (P2K2). This research uses library research through a methodology that combines the characteristics of various scientific sources accurately and validly to analyze facts by taking previous literature and reporting new facts and analysis. Primary, secondary, and tertiary materials to process and analyze data by describing and combining it so that it is presented in a journal manuscript. Data shows that the family capacity building meetings (P2K2) held every month by PKH social assistants for beneficiary families (KPM) who are members of groups in each assisted area receive a good response because KPMs receive non-formal education from health and Nutrition Module, ModuleEducation and Child Care, Family Financial Management Module, Child Protection Module, Social Welfare Module, and Prevention and TreatmentStanting. 6 Modules that are provided continuously every month can increase positive practices and then gradually change the behavior of beneficiary families. The Hope Family Programme in Indonesia will be a model for how to develop the capacity of people in different countries by means of meetings to enhance the ability of families. (P2K2).